Popular Music in Contemporary Church Chants - Zosim, Olga (Journal of History Culture and Art Research, 2020)
A feature of contemporary Christian music is its stylistic pluralism. Today, the most controversy is about the possibility of using in church chants various styles of popular music, which, at first glance, are less suitable for religious communication, which requires contemplation, spiritual recollection, and concentration from a person. The transformation of church music in the second half of the 20th century associated with globalization processes that led to an increase in interest in non-European cultures. The renewal of Christian music took the path of actualizing its ecstatic component, characteristic of Eastern culture and lost by Christianity many centuries ago. It was became the connecting link that made it possible to combine the forms and techniques tested in mass music with church tradition and contemporary church practice. A new type of liturgical music has become most sought after by Protestants, in the church services of which the central place is occupied by preaching with the proclamation of the Word of God. The rejection by the conservative part of parishioners of innovations in liturgical music gave rise to such a phenomenon as youth Christian music, which very soon went beyond the framework of the Protestant denomination and became a hallmark of the contemporary church practice of most Christian denominations. In the Catholic churches of the Western and Eastern rites, new church music is very popular, and it is rarely heard in the Roman Catholic liturgy and is never used in the Greek Catholic. Such restrictions are explained by the connection of church rites with the sacrament of the Eucharist, which requires prayer concentration, and not a dispersal of attention and spiritual relaxation. Youth Christian music is heard mainly in prayer meetings, in pilgrimages, during religious processions. The least characteristic is the style of contemporary popular music for church songs of the Orthodox Church, which is the most conservative and, when updating the repertoire, focuses on the style layer not of world pop music, but national cultural traditions.